Discontinuity in Learning : - English, Andrea R. (CUP, 2013)
"In this groundbreaking book, Andrea R. English challenges common assumptions by arguing that discontinuous experiences, such as uncertainty and struggle, are essential to the learning process. To make this argument, Dr. English draws from the works of two seminal thinkers in philosophy of education - nineteenth-century German philosopher J. F. Herbart and American Pragmatist John Dewey. English's analysis considers Herbart's influence on Dewey, inverting the accepted interpretation of Dewey's thought as a dramatic break from modern European understandings of education." --